Vasa Previa: Prenatal Diagnosis and Outcomes: Thirty‐five Cases From a Single Maternal‐Fetal Medicine Practice. (19th October 2017) - Kulkarni, Ankita; Powel, Jennifer; Aziz, Michael; Shah, Leena; Lashley, Susan; Benito, Carlos; Oyelese, Yinka
Abstract : Objectives: To assess the accuracy and effectiveness of routine screening for vasa previa, to describe our experience, and to assess factors that contribute to missed cases of vasa previa. Methods: A retrospective descriptive study of all cases of vasa previa from a single maternal‐fetal medicine service between 2009 and 2017 was performed. Ultrasound findings and obstetric and neonatal outcomes were reviewed and analyzed. Results: Thirty‐five cases of vasa previa were identified. Most cases (33 of 35 [94.3%]) were diagnosed antenatally. All 33 cases that followed our screening protocol were diagnosed antenatally and had favorable outcomes. Two cases that did not follow our protocol were not diagnosed antenatally and were delivered emergently. The mean gestational age ± SD at delivery of antenatally diagnosed cases was 34.9 ± 1.69 weeks. All neonates survived. Conclusions: Routine ultrasound screening for vasa previa using American Institute of Ultrasound in Medicine criteria will almost universally lead to good outcomes and prevent perinatal mortality.